Spatial assessment of growth and instability of livestock products in India - SRIVASTAVA, SANJIVANI; CHAUDHARY, SHWETA; SRIVASTAVA, S K; SINGH, H N (The Indian Journal of Animal Sciences, 2024)
Past studies regarding the growth and instability in production of livestock products have been conducted either for India or the major producing states. Therefore, the present study was conducted to estimate the growth and instability in production of milk, meat and egg, across all the states of India. The study is based on secondary data for a period ranging from 2000-01 to 2019-20. Percentage change, exponential growth function and Cuddy-Della Valle Index were utilized for calculating the relative growth rates, annual growth rates and level of instability. Results revealed that at the country level, India had achieved significant growth alongside low instability in its production of milk, meat and egg. However, large variations in growth rates and per-capita availabilities were detected at the state level. Current production levels of meat and egg were found inadequate in the majority of Indian states. Furthermore, an instability in production of meat and egg was observed in several states. The study recommends an inclusive and thorough execution of various livestock schemes along with timely transfer of credit and other extension services to reduce the inter-state disparities in livestock production. States with high level of instability in production must work on plugging the gap in their backward linkages, while states exhibiting low instability can focus on the processing of these highly perishable commodities.